Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fnins.2022.845737
|View full text |Cite
|
Sign up to set email alerts
|

The Effect and Optimal Parameters of Repetitive Transcranial Magnetic Stimulation on Poststroke Dysphagia: A Meta-Analysis of Randomized Controlled Trials

Abstract: ObjectiveThe objectives of the study were to evaluate the efficacy of repetitive transcranial magnetic stimulation (rTMS) treatment for poststroke dysphagia (PSD) and explore the optimal stimulation parameters.MethodThe databases of Medline, Embase, Web of Science, and Cochrane Library were searched from the establishment to June 2021. All randomized controlled trials about rTMS treatment for PSD were enrolled. Dysphagia Grade (DG) and Penetration Aspiration Scale (PAS) were applied as the major dysphagia seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…For example, noninvasive brain stimulation (NIBS), including repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS), is a practical technique which has proved effective, and is widely used to promote the recovery of PSD [ 56 ]. However, the rTMS relies on accurate stimulation at specific brain regions to achieve clinical efficacy [ 57 ]. Therefore, the insular cortex may become the target in the treatment of PSD and aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…For example, noninvasive brain stimulation (NIBS), including repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS), is a practical technique which has proved effective, and is widely used to promote the recovery of PSD [ 56 ]. However, the rTMS relies on accurate stimulation at specific brain regions to achieve clinical efficacy [ 57 ]. Therefore, the insular cortex may become the target in the treatment of PSD and aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…Transcranial magnetic stimulation may induce cortical plasticity in the human brain networks involved in language function, thus promoting language improvement (Szaflarski et al, 2021 ). In contrast, for post-stroke dysphagia, early rTMS intervention may better facilitate recovery (Qiao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A minimum number of five sessions seems to be required for rTMS to obtain a significant clinical benefit on dysphagia [99 ▪▪ ]. However, future studies are needed to define the optimal duration of NIBS treatment.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Conflicting findings are partly because of the low number of studies, assessing the therapeutic effects of low-frequency rTMS [106]. Furthermore, it should be considered, which hemisphere is stimulated: Qiao et al [99 ▪▪ ] found that while high-frequency rTMS can improve dysphagia when applied to the ipsilesional hemisphere (i.e. the damaged hemisphere), low-frequency rTMS is mainly effective when applied to the contralesional hemisphere (i.e.…”
Section: Treatment Strategiesmentioning
confidence: 99%